2020
DOI: 10.2147/opth.s264669
|View full text |Cite
|
Sign up to set email alerts
|

<p>Optical Coherence Tomographic Patterns as Predictors of Structural Outcome After Intravitreal Ranibizumab in Diabetic Macula Edema</p>

Abstract: Background/Objectives: The purpose of this study was to present an association between the treatment response of diabetic macular edema (DME) to intravitreal ranibizumab (IVR) injections and different morphology patterns using spectral domain optical coherence tomography (SD-OCT). Subjects/Methods: This retrospective study included 216 eyes of 142 subjects who received IVR for DME and were observed for at least 2 years. Medical charts and SD-OCT images of consecutive patients were reviewed at baseline, 1, 3, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…19 Chen et al found that studied cases with OCT results of HRF, hyperlipidemia, & coronary artery disease had less improvement in CMT at twoyear follow-up after intravitreal ranibizumab injection. 14 In our study, 66.67% in group 1, 73.33% in group 2 had interrupted inner segment/ outer segment (IS/OS) layer. Zur et al suggested that eyes with continuous IS-OS layers had a good response 2 months after intravitreal dexamethasone implant.…”
Section: Octmentioning
confidence: 45%
“…19 Chen et al found that studied cases with OCT results of HRF, hyperlipidemia, & coronary artery disease had less improvement in CMT at twoyear follow-up after intravitreal ranibizumab injection. 14 In our study, 66.67% in group 1, 73.33% in group 2 had interrupted inner segment/ outer segment (IS/OS) layer. Zur et al suggested that eyes with continuous IS-OS layers had a good response 2 months after intravitreal dexamethasone implant.…”
Section: Octmentioning
confidence: 45%
“…The CMT outcome at 2 nd year follow-up showed an average of 390.5 ± 75.3 µm in VIMA group, patients with morphological changes, which had considerable discrepancy in our previous work of favorable improvement in reduction of CMT in VMIA group with consistent IVR injections (13). This nding implies that patients with poor response, underlying physical mechanisms of pathogenesis other than VEGF may be involved and receive bene t from the treatment of surgical relief of traction (27).…”
Section: Discussionmentioning
confidence: 59%
“…Both ERM and VMT presented as a highly re ective band or membrane on the retinal surface. All patients were classi ed into four groups based on the OCT ndings, as our previous work have mentioned (13). DRT group included patients with only pure DRT.…”
Section: Outcome Measurementmentioning
confidence: 99%
“…Optical coherence tomography (OCT) and OCT angiography (OCTA) allow non-invasive recognition of imaging features that define a “DME profile”, distinguishing an inflammatory DME pattern characterized by the presence of subretinal fluid (SRF) and a high number of hyper-reflective foci (HRF) [ 4 , 5 ]. Furthermore, numerous imaging (OCT and OCTA) biomarkers have been identified in DME eyes as predictive of treatment response or disease progression, such as the retinal thickening characteristics [ 3 , 6 , 7 ], the presence, position, and internal reflectivity of microaneurysms (MAS) [ 8 , 9 ], the vitreomacular interface abnormalities (VMIAs) [ 6 ], the ellipsoid zone/external limiting membrane (EZ/ELM) integrity/disruption [ 7 ], the presence of nonperfusion areas (NPAs) [ 10 , 11 ], the foveal avascular zone (FAZ) abnormalities in terms of circularity and dimension [ 12 ], the involvement of deep capillary complex (DCP) [ 10 , 13 ], and the suspended scattering particles in motion (SSPiM) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%